Assessment of Radiation Hazard Indices Due to Natural Radionuclides in Soil Samples from Imo State University, Owerri, Nigeria - Benedict Chukwudi Eke; Idowu Richard Akomolafe; Udoka Mathias Ukewuihe; Chibueze Paul Onyenegecha (SAGE Publishing, 2024)
A total of 30 soil samples from different sampling points at Imo State University (IMSU), Owerri, Nigeria were collected for the study. The activity concentrations of naturally occurring radionuclides ( 238 U, 232 Th, and 40 K) were measured in the samples by gamma-ray spectrometry using NaI (TI) detector. Absorbed dose rate (D), annual effective dose (AED), radium equivalent activity (Ra eq ), and radiological hazard index parameters (activity utilization index [AUI], external hazard index [H ex ], internal hazard index [H in ], and excess lifetime cancer risk [ELCR]) due to the naturally occurring radionuclides were determined. The mean activity of 238 U, 232 Th, and 40 K were found to be 20.32 ± 3.22, 22.55 ± 0.68, and 91.63 ± 1.54 Bqkg −1 which were lower than the world average reference mean values of 33, 45, and 420 Bqkg −1 for 238 U, 232 Th, and 40 K, respectively, as reported by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). The average value of D, Ra eq , AUI, ELCR, H ex , and H in in the soil samples was 26.86 ± 1.97 nGyh −1 , 59.62 ± 4.14 Bqkg −1 , 0.42 ± 0.03, 0.14 ± 0.01 (×10 −3 ), 0.16 ± 0.01, and 0.22 ± 0.02, respectively. The annual effective dose to the general public was 33.07 ± 2.40 μSvy −1 . This value lies well below the average worldwide reference value of 0.7 mSvy −1 , as reported by UNSCEAR. Soil samples from IMSU pose no significant radiological health hazards to the university community.